Evaluation of Rock-Coring Capacity of Different Specifications of Core Drilling Tools - Huang, Wei; Liu, Bin; Yao, Kunpeng (International Journal of Mechanical and Electrical Engineering, 2024)
In order to solve the problem of low rock carrying efficiency of coring drilling tools in the process of coring operation under extreme ultra-high temperature and high-pressure environment, and considering the key rock carrying parameters such as coring bit type, cuttings particle size, drilling speed and drilling fluid viscosity in different formations, the three-dimensional model and flow field coupling model of coring tools with different specifications are established. The finite element method is used to evaluate the rock carrying capacity of the annulus of the coring outer cylinder. The results show that for the same type of coring tools, reducing the particle size of cuttings, increasing the viscosity of drilling fluid and reducing the drilling speed can reduce the volume fraction of residual cuttings and improve the rock carrying capacity of coring tools. For the 121,140,172 type coring tools, when the two drilling speeds are 0.8 m/h and 2.1 m/h respectively, the rock carrying capacity gap decreases with the increase of cuttings particle size. When the two drilling speeds of 203 type coring tools are 0.8m/h and 2.1m/h respectively, the difference of rock carrying capacity increases with the increase of cuttings size.